An Overview of the Diagnosis and Management of Seborrheic Dermatitis - Dall'Oglio F; Nasca MR; Gerbino C; Micali G (Dove Medical Press, 2022)
Federica Dall'Oglio, Maria Rita Nasca, Carlo Gerbino, Giuseppe Micali Dermatology Clinic, University of Catania, Catania, ItalyCorrespondence: Giuseppe Micali, Dermatology Clinic, University of Catania, Via S. Sofia 78, Catania, 95123, Italy, Tel + 39 095 321705, Fax + 39 095 3782425, Email cldermct@gmail.comAbstract: Seborrheic dermatitis (SD) is a common chronic inflammatory skin disorder that mostly affects young adults in areas rich in sebaceous glands (scalp, face, and trunk). In adolescents and adults, SD clinical presentation may range from mild patches to diffuse scalp scaling. In infants, it mainly occurs on the scalp as yellowish, scaly patches ("cradle cap"). In adults, several environmental triggers are likely to promote SD development, along with fungal colonization by Malassezia spp., sebaceous gland activity, as well as immunosuppression, endocrine, neurogenic and iatrogenic factors. In children, early occurrence in the first trimester suggests the role of excessive sebaceous gland activity from maternal hormones, along with cutaneous microbiome alterations. The diagnosis of SD is usually clinical, and specific laboratory and/or instrumental investigations are seldom required. Treatment is aimed at modulating sebum production, reducing skin colonization by Malassezia spp., and controlling inflammation. In adults, mild-to-moderate scalp SD forms can be managed with topical antifungals (ketoconazole, ciclopirox, miconazole) or antiinflammatory (mild-to-moderate potency corticosteroids) or keratolytic/humectant (propylene glycol) agents. Recommended topical therapeutic options for mild-to-moderate facial or body areas SD include topical ketoconazole, ciclopirox, clotrimazole, mild-to-moderate potency corticosteroids, lithium succinate/gluconate, and topical calcineurin inihibitors (off-label use). In severe and/or resistant cases, the use of systemic antifungal drugs (terbinafine, itraconazole), as well as UVB phototherapy, may be considered. In children, scant scientific evidence supports the effectiveness and safety of topical drugs, and "cradle cap" is usually successfully managed with baby shampoos enriched with emollient agents and vegetable oils. Alternatively, similarly to adult scalp SD, medical device shampoos with antiinflammatory and antifungal properties, containing piroctone olamine, bisabolol, alyglicera, telmesteine, may be used. Beyond pharmacological treatments, an appropriate cosmetic approach, if correctly prescribed, may improve therapeutic outcomes.Keywords: seborrheic dermatitis, diagnosis, therapy, topical, systemic, cosmetics